2023
DOI: 10.3389/fendo.2023.1226458
|View full text |Cite
|
Sign up to set email alerts
|

G protein–coupled estrogen receptor: a promising therapeutic target for aldosterone-induced hypertension

Xuehan Li,
Wenlong Kuang,
Zhihua Qiu
et al.

Abstract: Aldosterone is one of the most essential hormones synthesized by the adrenal gland because it regulates water and electrolyte balance. G protein–coupled estrogen receptor (GPER) is a newly discovered aldosterone receptor, which is proposed to mediate the non-genomic pathways of aldosterone while the hormone simultaneously interacts with mineralocorticoid receptor. In contrast to its cardio-protective role in postmenopausal women via its interaction with estrogen, GPER seems to trigger vasoconstriction effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Furthermore, Elisa Schena et al [24] have recently shown that the mineralocorticoid receptor is a new player in FPLD2. Interestingly, it has been reported that the G protein-coupled estrogen receptor (GPER) is a newly discovered aldosterone receptor, which is proposed to mediate the non-genomic pathways of aldosterone while interacting with estrogen [25]. Although this is not proof of the putative role of estrogens in modulating lamin A function on adipose tissue, it probably paves the way for future studies on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Elisa Schena et al [24] have recently shown that the mineralocorticoid receptor is a new player in FPLD2. Interestingly, it has been reported that the G protein-coupled estrogen receptor (GPER) is a newly discovered aldosterone receptor, which is proposed to mediate the non-genomic pathways of aldosterone while interacting with estrogen [25]. Although this is not proof of the putative role of estrogens in modulating lamin A function on adipose tissue, it probably paves the way for future studies on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GPER is a newly discovered aldosterone receptor that is believed to mediate nongenomic aldosterone pathways. GPER activation by aldosterone mediates water and sodium retention in the body and contributes to vasoconstriction [220]. Recently it has been shown that production of aldosterone may be influenced by progesterone [221].…”
Section: Interaction Of Avp and Steroids In Regulation Of Water-elect...mentioning
confidence: 99%
“…These effects comprise the dilatory actions of aldosterone mediated via the endothelium (e.g., the generation of nitric oxide) and direct constrictor effects on vascular smooth muscle cells [ 13 ]. The latter is, at least in part, mediated by the newly discovered G protein–coupled estrogen receptor (GPER) [ 29 ]. The net effect of aldosterone on vascular resistance depends on the location of the specific vessel, the concentration of aldosterone, and the exposure time [ 32 ].…”
Section: Introductionmentioning
confidence: 99%